Inverter-Side Current Control of Grid-Connected Voltage Source Inverters With LCL Filter Based on Generalized Predictive Control - Judewicz, Marcos (2018)
In this paper, an inverter-side current (ISC) control strategy for grid-connected voltage source inverter with LCL filters is proposed based on a generalized predictive control (GPC) formulation as it has the advantages of fixed switching frequency, a systematic design procedure and low computational complexity. As the GPC strategy is a subtype of continuous-control-set model predictive control strategies, a proper model for controlling the ISC is obtained, showing that a full-order model is preferred to its first-order counterpart. The controller is designed taking into consideration harmonic distortion limits and robustness against filter component variations. To this end, a complete three-wire LCL filter model is obtained and impedance sensitivity to each component variation is analyzed. Finally, its performance is evaluated by means of experimental results and compared with a predictive deadbeat controller.